(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2020)
This essay addresses some efforts of the Government of Reconciliation and National Unity of Nicaragua in the development of programs and projects that today benefit thousands of Nicaraguan citizens with free and quality higher education. From this approach, we will examine the government strategies that have made many students dreams come true, forming them professionally from the virtual modality, thus contributing to the economic development of their families and their country. Education is a right that every human being must possess, without any social, political or religious exclusion. Education is a responsibility of all governments in the world and they must ensure a free and inclusive education.